2018
DOI: 10.1097/rlu.0000000000001886
|View full text |Cite
|
Sign up to set email alerts
|

Role of Various Metabolic Parameters Derived From Baseline 18F-FDG PET/CT as Prognostic Markers in Non–Small Cell Lung Cancer Patients Undergoing Platinum-Based Chemotherapy

Abstract: Baseline MTV and TLG evaluated from primary tumor as well as the whole-body tumor lesions are reliable prognostic markers of OS in NSCLC patients undergoing platinum-based chemotherapy. However, other baseline whole-body PET/CT parameters (SUVmax, average SUV, and tumor-to-background ratio) and dynamic PET/CT parameters (net influx rate constant, glucose metabolic rate) have no prognostic value in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 25 publications
2
44
0
Order By: Relevance
“…This may be due to the fact that SUVmax-T only represented a few pixels instead of the whole tumour. Studies showed that among PET biomarkers, metabolic tumor volume (MTV) and total lesion glycolysis (TLG) both re ect the metabolic tumor burden and are considered to be the strongest prognostic factors, even more so than tumoral maximal standardized uptake values (SUVmax) [13]. Some studies have shown that MTV or TLG, after taking the tumour size into consideration, are better prognostic predictors than SUVmax alone [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the fact that SUVmax-T only represented a few pixels instead of the whole tumour. Studies showed that among PET biomarkers, metabolic tumor volume (MTV) and total lesion glycolysis (TLG) both re ect the metabolic tumor burden and are considered to be the strongest prognostic factors, even more so than tumoral maximal standardized uptake values (SUVmax) [13]. Some studies have shown that MTV or TLG, after taking the tumour size into consideration, are better prognostic predictors than SUVmax alone [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have focused on the correlation of metabolic parameters such as the standard uptake values (SUVs) of gross tumours and survival outcomes in patients with ESCC but have reached controversial conclusions. A meta-analysis that included 10 studies concluded that a high maximum of standard uptake value (SUVmax) of the primary tumour predicted a poor overall survival with a hazard ratio of 1.86 (95%CI,1.53-2.27), but the cut-point to de ne a high SUV ranged widely in these studies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) [6]. A multi-centre prospective study reported that the SUV of the baseline gross tumour had a negative prognostic value in oesophageal cancer patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…The FDG‐PET is a superior modality for detecting malignant lesions in the digestive tract and other sites 15, 16, 17, 18, 19. FDG‐PET can be used for imaging of tumor activity by reflecting glucose metabolism; rarely, it can also be used to obtain a functional imaging diagnosis of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The largest study (311 patients, UICC stage I-III) further showed that ASP, with an optimal cut-off of > 19.5%, could identify patients with UICC stage II treated by surgery and adjuvant chemotherapy with high ASP and reduced PFS (median, 11 months vs. not reached) and OS (22 months vs. not reached) (15). ASP was superior for survival prediction compared to primary tumor's maximum standardized uptake value (SUVmax) and MTV, two other previously proposed and common PET parameters (8,9,16,17).…”
Section: Introductionmentioning
confidence: 96%